ANALISIS PENERAPAN GREEN BUILDING PADA BANGUNAN PENDIDIKAN (STUDI KASUS : GREEN SCHOOL BALI) - Hapsari, Oktavi elok (Al-Ard: Jurnal Teknik Lingkungan, 2018)
Green building concept is a discourse that is expected to address the challenges of today development. The formulated of Green Building in these six criteria can be used as a guide to produce a sustainable design. The six criteria are Rightness Land Use, Energy Efficiency and Conservation, Water Conservation, Material Sources & Cycles, Air Quality and Air Comfort in Space and Building Environmental Management. Green School Bali is buildings that perform green building. This educational institution has an concept that is combined education toward the environment create a healthy environment. This study aims to knowing the application of green building in the Green School Bali to use as a reference in designing. The research method used is literature study to analyze buildings. The results show that Green School Bali has implemented the six criteria of green building, especially in building design that can save energy consumption and use of bamboo materials in the entire building. Keywords: Green Building Concept, Green School Bali, Bamboo